Diagnostic Applications of Cone-Beam CT for Periodontal Diseases - Yousef A. AlJehani (International Journal of Dentistry)
Objectives. This paper aims to review the diagnostic application of cone beam computed tomography (CBCT) in the field of periodontology. Data. Original articles that reported on the use of CBCT for periodontal disease diagnosis were included. Sources. MEDLINE (1990 to January 2014), PubMed (using medical subject headings), and Google Scholar were searched using the following terms in different combinations: “CBCT,” “volumetric CT,” “periodontal disease ,” and “periodontitis.” This was supplemented by hand-searching in peer-reviewed journals and cross-referenced with the articles accessed. Conclusions. Bony defects, caters, and furcation involvements seem to be better depicted on CBCT, whereas bone quality and periodontal ligament space scored better on conventional intraoral radiography. CBCT does not offer a significant advantage over conventional radiography for assessing the periodontal bone levels.